Designing Two‐Dimensional Nanosheets for Improving Drug Delivery to Fucose‐Receptor‐Overexpressing Cancer Cells. (6th December 2018) - Gupta, Nitin; Jangid, Ashok Kumar; Singh, Mandeep; Pooja, Deep; Kulhari, Hitesh
Abstract: Targeted drug delivery has shown promise in improving the therapeutic efficacy of anticancer drugs. Gemcitabine hydrochloride (GEM) is a broad‐range chemotherapeutic agent for the treatment of various cancers. However, systemic use of free GEM is restricted because of its poor physicochemical properties and nonspecific drug delivery, resulting in dose‐dependent adverse effects. In this study, a fucose‐conjugated graphene oxide (GO)‐based smart targeted nanocarrier system was designed to provide high loading, sustained release, and targeted high concentrations of GEM to cancer cells. Fucose‐conjugated GO nanosheets (FGONS) and GEM‐loaded fucose‐conjugated GO nanosheets (GEM‐FGONS) were prepared and characterized by various techniques. About 36.2 % of GEM was loaded to the FGONS, which showed a pH‐dependent release over a period of 48 h. A colloidal suspension of GEM‐FGONS was found to be physiochemically stable for up to 96 h. In cytotoxicity studies, GEM‐FGONS demonstrated time‐ and dose‐dependent high toxicities on fucose‐receptor‐overexpressing MDA‐MB‐231 human breast cancer cells and A549 human lung cancer cells. Moreover, targeted formulations were more efficacious than non‐targeted or free GEM. Overall, bioconjugation of fucose helps in the stabilizing and targeting of graphene oxide nanosheets. Abstract : Keeping stable, steady aim : a fucose‐conjugated graphene oxide (GO)‐based smart targeted nanocarrier system was designed to provide high loading, sustained release, and targeted high concentrations of GEM to cancer cells. Fucose‐conjugated GO nanosheets (FGONS) and GEM‐loaded fucose‐conjugated GO nanosheets (GEM‐FGONS) were prepared and characterized by various techniques, showing that bioconjugation of fucose helps in the stabilizing and targeting of graphene oxide nanosheets.